Evaluasi Lahan Pembudidayaan Rumput Laut di Perairan Kampung Sakabu, Pulau Salawati, Kabupaten Raja Ampat - Dimara, Wihelmina; Ngangi, Edwin D; Mondoringin, Lukas L.J.J (Universitas Sam Ratulangi, 2014)
The objective of this research was to evaluate the suitability of several environment factors and water quality parameters for development of seaweed culture in Kampung Sakabu. The research was conducted through observation at three stations while protection factor and bottom substrate of waters were observed visually. Water quality parameters including pH, salinity, current rate, temperature were measured in situ and the compared to Standard Water Quality Citeria by Bakosurtanal 1996. Research results were divided into three suitability categories namely 1) very suitable, 2) suitable, and 3) less suitable. In general, environmental condition and water quatily in Kampung Sakabu were categorized as suitable to very suitable. This results indicated that waters of Kampung Sakabu was very potential for development of seaweed culture. Keywords: Kampung Sakabu, seaweeds, area suitability, water quality